E-106 Outcome of mechanical thrombectomy when IV thrombolysis is not eligible. (22nd July 2019) - Sung, J; Lee, M; Lee, D; Lee, H; Yang, S
Abstract : Introduction: Mechanical thrombectomy (MT) after intravenous thrombolysis (IVT) is recommended in acute ischemic stroke (AIS) patients with large artery occlusion (LAO). But in cases of ineligible for IVT, MT is the only option. The aim of this study is to evaluate the efficacy and outcome of MT in case of ineligible for IVT. Method: Retrospective analysis was performed in consecutive patients treated between January 2016 and November 2018 for AIS with LAO. Patient demographic data were collected and clinical outcome, procedure details and complication rate were compared. Results: During the period, 80 patients were visited within 4.5 hours from onset, but only 31 underwent MT alone due to contraindication (MT group). And 49 underwent MT combined IVT (MTIVT group). There was no significant difference in demographics and complication (distal emboli, mortality rate, symptomatic intracranial hemorrhage). The mean time from onset to groin puncture, successful reperfusion rate (defined thrombolysis in cerebral infarction 2b/3) and favorable functional outcome (determined by modified Rankin Scale score 0–2 at 90 days) also showed no significant statistically difference. But MT group had a significantly shorter mean procedure time (45.84 vs. 76.06 min; p = 0.001) and hospital stay (11.53 vs. 15.0 day; p = 0.042), and a lower 1-day NIHSS score (6.35 vs 10.88; p = 0.012). Conclusion: In ineligible patient for IVT, MT alone isn't inferior to MT combined with IVT. Disclosures: J. Sung: None. M. Lee: None. D. Lee: None. H. Lee: None. S. Yang: None.